2021
DOI: 10.3390/pharmaceutics14010064
|View full text |Cite
|
Sign up to set email alerts
|

N-Alkylmorpholines: Potent Dermal and Transdermal Skin Permeation Enhancers

Abstract: Transdermal drug delivery is an attractive non-invasive method offering numerous advantages over the conventional routes of administration. The main obstacle to drug transport is, however, the powerful skin barrier that needs to be modulated, for example, by transdermal permeation enhancers. Unfortunately, there are still only a few enhancers showing optimum properties including low toxicity and reversibility of enhancing effects. For this reason, we investigated a series of new N-alkylmorpholines with various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Among chemical compounds that increase the permeability of the skin to drugs are those otherwise known as chemical penetration enhancers (CPEs) or sorption promoters: terpenes, terpenoids, sulfoxides, laurocapram (Azone), pyrrolidones, fatty acids, fatty alcohols, alcohols containing glycols, urea, and surfactants. , In 2021, 649 compounds classified as CPEs were collected in a database which included the following groups of chemicals: alcohols and polyols, lactams and their analogues (azepane, azone, caprolactam, morpholine, piperazine, piperidine, piperidone, pyrrolidine, pyrrolidone, and succinimide), esters and ethers, fatty acids, terpenes and steroids, and miscellaneous additives such as amino acids, aliphatic compounds, aromatic compounds, and inorganic compounds . However, some of the listed groups of compounds, primarily morpholine and morpholine derivatives and among them Azone, surfactants, aromatic compounds, and many others, carry the risk of causing skin irritation, permanent disorganization of the skin barrier, and toxic effects on skin cells. These effects may not be acceptable in the application of transdermal drug delivery systems to the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Among chemical compounds that increase the permeability of the skin to drugs are those otherwise known as chemical penetration enhancers (CPEs) or sorption promoters: terpenes, terpenoids, sulfoxides, laurocapram (Azone), pyrrolidones, fatty acids, fatty alcohols, alcohols containing glycols, urea, and surfactants. , In 2021, 649 compounds classified as CPEs were collected in a database which included the following groups of chemicals: alcohols and polyols, lactams and their analogues (azepane, azone, caprolactam, morpholine, piperazine, piperidine, piperidone, pyrrolidine, pyrrolidone, and succinimide), esters and ethers, fatty acids, terpenes and steroids, and miscellaneous additives such as amino acids, aliphatic compounds, aromatic compounds, and inorganic compounds . However, some of the listed groups of compounds, primarily morpholine and morpholine derivatives and among them Azone, surfactants, aromatic compounds, and many others, carry the risk of causing skin irritation, permanent disorganization of the skin barrier, and toxic effects on skin cells. These effects may not be acceptable in the application of transdermal drug delivery systems to the skin.…”
Section: Introductionmentioning
confidence: 99%
“…That can be due to the enhancing effect of ethanol in the formulation, which can disrupt the skin barrier more and thus enable the passage of API through the skin more effectively than other formulations. Although the reversal was not as fast and clear as for other formulations, the incorporation of ethanol in ethosomes showed lower effects on the barrier properties than even traditional and novel permeation enhancers [ 44 ]. LNC and PNP showed levels of alternation comparable to the PBS.…”
Section: Resultsmentioning
confidence: 99%
“…If it is the latter, one must find out how long it takes for the skin barrier to return to its original properties. Such reversibility measurements are well established in the evaluation of permeation enhancers [ 44 , 75 , 78 ]. Nanoformulations are also a type of enhancing system; therefore, we conducted a reversibility study, where we observed the TEWL of skin treated for 24 h by all three nanosystems (ETZ, PNP, and LNC) and hydrated by PBS as a control and then measured the same in set time intervals up to 24 h after the removal of the formulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the formulation on skin integrity was investigated by conducting TEWL measurements before applying the formulation to the donor side and at the conclusion of the study, following established protocols [37].…”
Section: In Vitro Skin Permeation Studymentioning
confidence: 99%